WPF Recipes in C# 2008 - Bourton, Sam (Springer, 2017)
Windows Professional Foundation (WPF) offers amazing opportunities to .NET programmers in terms of the user interfaces they can deliver to their customers. But this significant technological advance comes with a steep learning curve, requiring the programmer to learn new classes, new syntax, and an entirely new approach to user interface development.